On the Fundamental Possibility of a Supersonic Civil Aircraft to Comply with ICAO Noise Requirements Using Existing Technologies - Victor F. Kopiev; Ivan V. Belyaev; Andrey I. Dunaevsky; Andrey A. Poukhov; Igor L. Trofimovsky (Aerospace, 2022)
Compliance with environmental protection regulations, in particular, community noise requirements, constitutes one of the major obstacles for designing future supersonic civil aircraft. Although there are several noise sources that contribute to the total noise level of supersonic aircraft, it is the turbulent jet that appears most problematic; jet noise is a dominant noise source for low-to moderate- bypass-ratio engines, and at present there are no effective methods of jet noise reduction other than decreasing jet speed by increasing bypass ratio, which, in turn, is constrained by aerodynamic requirements for supersonic flight. The present study considers a concept of supersonic civil aircraft under the assumption that its total noise is determined by turbulent jets; it is shown that compliance of the supersonic aircraft with the current regulations for subsonic aircraft noise (Chapter 14 Volume I Annex 16 ICAO) would require the decreased jet speed that corresponds to a prohibitively high bypass ratio of aircraft engines. To enable jet noise reduction without necessarily increasing bypass ratio, a novel configuration of supersonic aircraft is proposed that meets the requirements of Chapter 14, thereby demonstrating that the norms of Chapter 14 are achievable for future supersonic civil aircraft with the use of existing technologies.